-(x+2)=5x+3x-11

Simple and best practice solution for -(x+2)=5x+3x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+2)=5x+3x-11 equation:



-(x+2)=5x+3x-11
We move all terms to the left:
-(x+2)-(5x+3x-11)=0
We add all the numbers together, and all the variables
-(x+2)-(8x-11)=0
We get rid of parentheses
-x-8x-2+11=0
We add all the numbers together, and all the variables
-9x+9=0
We move all terms containing x to the left, all other terms to the right
-9x=-9
x=-9/-9
x=1

See similar equations:

| 3-5x=2x+3 | | -(3-6x)=-(-6x+3) | | 2^1+2x=0 | | x/35=180000 | | 9-7x=5x-87 | | -3(x+9)=-2(4x+5) | | (a+5)/3=13 | | 5x+8=43-2x | | x/35=180 | | -7(10+5x)=315 | | -7x+6=69+2x | | c+9c-88=180 | | 6(5x-3)=-18 | | C=9c-88 | | -9+4x=5x-19 | | 9x-(2x-10)=36 | | 3.5x+3.5x+2x=180° | | 4(6-2x)=48 | | 2.25=18/4x | | -3(-2-2x)=48 | | (5x-10)+3x=180 | | -1+3x=7x-9 | | u-8.6=4.62 | | m-3/2=-4 | | 3c-58=c | | 10•n=1.5 | | -5(5+7x)=-375 | | 3y-91=2y-53 | | 18x+16=-17+2x | | 15+3v=6v | | -78=w/8-87 | | 3z/7-9=7 |

Equations solver categories